Analisis Aplikasi Marbel Huruf Versi Mobile Terhadap Pembelajaran Membaca di Desa Semanding Ponorogo - Karaman, Jamilah; Setyanto, Arief; Sofyan, Amir Fatah (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
The development of technology, especially information and communication technology offers many ease-ease in learning, which allows the shift of learning orientation from the process of presenting various knowledge into the process of guidance in individual exploration of science. Interactive learning media for children who rampant today is a game-based learning pedia is "MARBEL". Marbel is an abbreviation of "Let's Learn", marbel application is an educational application (mobile learning) for children aged 2 to 8 years so that made mobile-based applications aims to facilitate children in the learning process.